Paediatric diaphyseal femur fracture treated with intramedullary titanium elastic nail system - Thapa, Shrawan Kumar; Poudel, Krishna Prasad; Marasini, Rudra Prasad; Dhakal, Shankar; Shrestha, Robin (Journal of College of Medical Sciences-Nepal, 2015)
no Background & Objectives: Over the few years there has been a marked increase in the use of intramedullary fixation in the management of fracture of shaft of femur in children. The goals should be to stabilize the fracture, to control length and alignment, to promote bone healing and to minimize the morbidity and complications for the child. In this prospective study we intend to evaluate the functional and radiological outcome of diaphyseal fracture of shaft of femur treated with elastic intramedullary nail. Materials & Methods: All 56 patients with diaphyseal fracture shaft of femur were treated with titanium elastic nail and followed for period of 32 weeks. Results: The In this study, outcome was assessed by using Flynn’s criteria of titanium flexible nail outcome score and we found excellent result in 49 cases, satisfactory in six cases and poor in one case. We faced one major complication in form of implant failure and six minor complications inform of superficial wound infection. Conclusion: Elastic intramedullary nail used in treatment of diaphyseal fracture shaft of femur yield excellent functional and radiological outcome. It is easy and simple procedure has low rate of complication. It is physeal-protective, cost effective, does not involve heavy instrumentation and can be performed in small set up. It has minimal risk of infection and no risk of injury to the neurovascular structure. JCMS Nepal. 2015; 11(2):20-22